PATYRIMO TERITORIJA. - Šliogeris, Arvydas (Problems / Problemos, 2007)
The author presents a hypothesis that experience is possible and even somehow inevitable exclusively in the area of direct sensuality. Man, as this particular body individuum, is fatally related to this area as he comes into direct contact with this particular thing that discloses its ineradicable non-humanity. Experience can be defined as a paralinguistic clash with absolute non-humanity which is rooted on this side of the sensual horizon and emerges in the form of a thing as a phenomenon of sensual transcendentality. Therefore, experience should be treated as a total opposite of instrumental relation with a thing. As experience cannot be produced or otherwise 'made', thus the conception of artificial (laboratorical) experience, which takes its origins from Kant and is rooted in techno-science, schould be discarded as an examplary model of any kind of experience. A specific area of experience should not be considered as a laboratory, a factory (or any of its prototypes such as church, workshop, monastery cell, library), a computer screen, or any other kind of 'reality show' but rather as mute things or ensembles of such things untouched by the human hand.